2014
DOI: 10.1093/europace/euu155
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related differences in presentation, treatment, and outcome of patients with atrial fibrillation in Europe: a report from the Euro Observational Research Programme Pilot survey on Atrial Fibrillation

Abstract: The EORP-AF Pilot survey provides contemporary data on sex differences in clinical features and management of AF patients participating in the EORP-AF Pilot registry. Female subjects were older and more symptomatic, compared with males, and were more likely to receive rate control. Also, female patients were at higher stroke risk overall, but oral anticoagulation was used in a high proportion of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
153
5
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 182 publications
(201 citation statements)
references
References 19 publications
21
153
5
7
Order By: Relevance
“…These findings are contrary to studies mentioned above, in which paroxysmal AF population had less often concomitant conditions. Sex differences in the epidemiology and clinical management of AF are evident and have been described in several studies [6,15,16]. In this analysis, we found that females were older, had more often IHD, severely impaired EF, previous MI and CABG.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…These findings are contrary to studies mentioned above, in which paroxysmal AF population had less often concomitant conditions. Sex differences in the epidemiology and clinical management of AF are evident and have been described in several studies [6,15,16]. In this analysis, we found that females were older, had more often IHD, severely impaired EF, previous MI and CABG.…”
Section: Discussionsupporting
confidence: 65%
“…In consequence, AF population remains a heterogenous group due to variety of clinical presentations and treatment options. In most of the reports and registries, AF is associated with at least one concomitant condition, most commonly with hypertension [6,7]. In our population, 97% of AF patients had at least one associated medical condition.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…При этом динамика параметров комплексного клинического и инструментального обследования определяется тяжестью состояния конкретного больного. Это положение не противоречит данным литературы [1, 7,8]. Можно утверждать, что полученные показатели ассоциируются с возникновения ПФП, а определение предикторов аритмии позволит более эффективно проводить профилактику ССО на ранних стадиях их развития [9,10].…”
unclassified